2020
DOI: 10.1126/scitranslmed.aaw7843
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in glioma macrophage populations after radiotherapy reveal CSF-1R inhibition as a strategy to overcome resistance

Abstract: Tumor-associated macrophages (TAMs) and microglia (MG) are potent regulators of glioma development and progression. However, the dynamic alterations of distinct TAM populations during the course of therapeutic intervention, response, and recurrence have not yet been fully explored. Here, we investigated how radiotherapy changes the relative abundance and phenotypes of brain-resident MG and peripherally recruited monocyte-derived macrophages (MDMs) in glioblastoma. We identified radiation-specific, stage-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 55 publications
(94 reference statements)
12
185
0
Order By: Relevance
“…CX3CR1 and CSF1R are highly expressed in FCGR3A + (CD16 + ) subset, which can be identified as an inflammatory phenotype in anti-tumor immune response [ 59 ]. Although in preclinical models of glioblastoma, targeting TAMs and microglia using CSF1R inhibitor combined with radiotherapy could enhance survival [ 60 ], might be not suitable for AML patients and impairs anti-tumor immune response [ 61 ]. This reminds us CSF1R inhibitors (such as BLZ945 and PLX3397) might not bring benefit to some AML patients (AML210A, AML329, and AML707B) without identifying major groups of CSF1R-expressing immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…CX3CR1 and CSF1R are highly expressed in FCGR3A + (CD16 + ) subset, which can be identified as an inflammatory phenotype in anti-tumor immune response [ 59 ]. Although in preclinical models of glioblastoma, targeting TAMs and microglia using CSF1R inhibitor combined with radiotherapy could enhance survival [ 60 ], might be not suitable for AML patients and impairs anti-tumor immune response [ 61 ]. This reminds us CSF1R inhibitors (such as BLZ945 and PLX3397) might not bring benefit to some AML patients (AML210A, AML329, and AML707B) without identifying major groups of CSF1R-expressing immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Once entrenched in the glioma microenvironment, these tumor-educated macrophages would support angiogenesis [12,13,75,84,85], a finding strengthened by the fact that they form physical contacts with blood vessels to a greater degree than microglia [75]. Additional work has revealed that the macrophage proportion increases in recurrent gliomas, potentially suggesting a macrophage functional role in mediating glioma recurrence after radiation [14]. While considerable work still needs to be done to uncover additional roles of these myeloid cells and to pave the way for tumor-specific therapy, mounting evidence seems to suggest specific and distinct roles for microglia and macrophages dependent on their localization within and around a tumor.…”
Section: Microglia and Macrophages: Partners In Crime Or Divergent Plmentioning
confidence: 99%
“…In lieu of pharmacological microglial activation, whole-brain radiation may also be used to induce microglia activation in an effort to promote synaptic pruning [61]. Unfortunately, it also appears that microglia are responsible for radiation-induced cognitive deficits and that elimination of microglia or CSF1R blockade reduces cognitive impairment and boosts radiation efficacy [14,16,[61][62][63]. Thus, while radiation may be used as a tool to study the effect of microglia on NGS, radiation will most likely not produce robust synaptic pruning once this treatment is paired with CSF1R antagonists in a clinical setting.…”
Section: Pilot Studies To Discern the Role Of Synapse Formation And Mmentioning
confidence: 99%
See 2 more Smart Citations